1999
DOI: 10.1111/j.1600-0838.1999.tb00205.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of injuries in young female players in European team handball. A prospective intervention study

Abstract: Young female players in European handball have a very high injury incidence, up to 50 injuries per 1000 hours of game. More than half of these injuries happen without any external cause. The aim of the study was to investigate the effect of an intervention programme designed to reduce the number of injuries in young female players in European handball, with special emphasis on injuries in the lower extremities. The programme was created using elite athlete training programmes and those designed for rehabilitat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
228
1
8

Year Published

2001
2001
2012
2012

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 271 publications
(246 citation statements)
references
References 10 publications
9
228
1
8
Order By: Relevance
“…Although a lot of studies proposed that a balance exercise program improve the balance ability deficits due to injury (Caraffa et al, 1996;Chong et al, 2001;Wedderkopp et al, 1999;Gioftsidou et al, 2006), there were found no studies measuring balance parameters and their possible improvements after an application of a specific balance exercise program in healthy professional handball male players.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Although a lot of studies proposed that a balance exercise program improve the balance ability deficits due to injury (Caraffa et al, 1996;Chong et al, 2001;Wedderkopp et al, 1999;Gioftsidou et al, 2006), there were found no studies measuring balance parameters and their possible improvements after an application of a specific balance exercise program in healthy professional handball male players.…”
Section: Discussionmentioning
confidence: 99%
“…Caraffa et al (1996) demonstrated in a prospective controlled study that the rate of ACL ruptures was remarkably reduced after introducing proprioceptive training on balance-boards to semiprofessional male soccer teams. Similarly, Wedderkopp and his partner (Wedderkopp et al, 1999) mentioned that the application of a balance training program on balance boards by healthy female handball players, for 10 months resulted in decrease of frequency of lower limb injuries.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations